in Quantitative Aptitude edited by
45 views
1 vote
1 vote

If $ f(x+y) = f(x) f(y) $ and $ f(5) = 4,$ then $ f(10) – f(-10) $ is equal to 

  1. $0$
  2. $15.9375$
  3. $3$
  4. $14.0625$
in Quantitative Aptitude edited by
by
1.3k points 5 6 33
45 views

1 Answer

1 vote
1 vote
Given that,

$ f(x+y) = f(x) f(y),$ and $f(5) = 4 $

Now, $ f(10) = f(5+5) $

$ \Rightarrow f(10) = f(5) f(5) $

$ \Rightarrow f(10) = 4 \times 4 $

$ \Rightarrow \boxed{ f(10) = 16} $

And, $ f(15) = f(5+10) $

$ \Rightarrow f(15) = f(5) f(10) $

$ \Rightarrow f(15) = 4 \times 16 $

$ \Rightarrow \boxed{ f(15) = 64} $

We can write $ f(5) = f[15+(-10)] $

$ \Rightarrow f(5) = f(15) f(-10) $

$ \Rightarrow 4 = 64 f(-10) $

$ \Rightarrow  f(-10) = \frac{4}{64}$

$ \Rightarrow \boxed{ f(-10) = \frac{1}{16}} $

Then, $ f(10) – f(-10) = 16 – \frac{1}{16} = \frac{256-1}{16} = \frac{255}{16}  = 15. 9375 $

$ \therefore$ The value of $f(10) – f(-10) = 15 . 9375.$

Correct Answer$: \text{B}$
edited by
by
4.9k points 3 7 28
Answer:

Related questions

Ask
Quick search syntax
tags tag:apple
author user:martin
title title:apple
content content:apple
exclude -tag:apple
force match +apple
views views:100
score score:10
answers answers:2
is accepted isaccepted:true
is closed isclosed:true